2018
DOI: 10.3390/land7020075
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Land Cover Change in Peri-Urban High Andean Environments South of Bogotá, Colombia

Abstract: Bogotá, the rapidly growing center of an emerging economy in the northern part of South America, is located within a biodiversity hotspot in the tropical Andes. The surrounding mountains harbor the ecosystems Páramo and Bosque Altoandino whose high water retention capacity serves as a "natural water tower" for the city's freshwater supply. Since Bogotá is steadily growing, the city spreads into its peri-urban area, thus threatening its proximal ecosystems. In this study, the land use and land cover change (LUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 140 publications
0
14
0
Order By: Relevance
“…A collection of 6139 random sample points was assembled, and the remaining outliers were removed because they were scattered outside of the rasters. Extracted distance proximity parameter values were log-transformed and, during computation, a 30 m value equivalent to cell length was added to all cells in order to counter undefined 0 logarithm for predictors applied in the regression analysis [46]. The statistical significance of p < 0.05 indicated that the relation between predictor and LULC change occurrences were not random, highlighting a statistical relation between the independent proximity variable and an urban built-up area.…”
Section: Binomial Logistic Regressionmentioning
confidence: 99%
“…A collection of 6139 random sample points was assembled, and the remaining outliers were removed because they were scattered outside of the rasters. Extracted distance proximity parameter values were log-transformed and, during computation, a 30 m value equivalent to cell length was added to all cells in order to counter undefined 0 logarithm for predictors applied in the regression analysis [46]. The statistical significance of p < 0.05 indicated that the relation between predictor and LULC change occurrences were not random, highlighting a statistical relation between the independent proximity variable and an urban built-up area.…”
Section: Binomial Logistic Regressionmentioning
confidence: 99%
“…When connected with GIS, binomial logistic regression is an appropriate tool for explanatory analysis of the factors of land cover changes [31,57,60]. Accordingly, we used logistic regression models to identify drivers and determining factors leading to vegetation cover changes.…”
Section: Binomial Logistic Regressionmentioning
confidence: 99%
“…The True Positive Rate gives the proportion of correctly classified positive sampling points. The True Negative Rate is the proportion of the correctly classified negative sampling points [31,61].…”
Section: Binomial Logistic Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…GIS provides a flexible environment for a rapidly developing data processing and analysing for change detection in a study area. In high-Andean mountains, most previous land-use change studies using GIS focused on a peri-urban interface [8], [9], or a watershed [10]- [14], or a specific ecosystem [15]- [18], but not much research has been done across multiple provincial boundaries. In Peru, land planning at local level is regulated by provincial municipalities (Organic Law of Municipalities No.…”
Section: Introductionmentioning
confidence: 99%